Corporate cash holdings and national culture: Evidence from the Middle East and North Africa region - Sherif El-Halaby; Hosam Abdelrasheed; Khaled Hussainey (Journal of Risk and Financial Management, 2021)
This paper investigates to what extent cultural dimensions, based on Hofstede's model, can clarify differences in cash holding levels. The sample includes 395 banks across 19 countries in the Middle East and North Africa region over a period of 16 years (1999-2014). The findings indicate that when uncertainty avoidance and masculinity decrease, cash holdings increase, whereas when power distance, long-term orientation, and individualism increase, the cash holdings increase correspondingly. Based on robustness analysis, the results remain unaffected even after controlling corporate and macroeconomic characteristics related to inflation, corruption, and the exchange rate system. Further analysis shows insignificant differences between Islamic and non-Islamic banks regarding the influence of culture over cash holdings. This study contributes to the literature regarding the impact of culture on corporate cash holdings based on a unique and different context, through examining this relationship in financial institutions located in the Middle East and North Africa region.
Keywords: 330; cash holdings; culture; Middle East and North Africa region